Storie sepolte: I deserti di Don DeLillo (TEST Ticontre. Theory Text Translation, 2022)
The paper explores the topic of the desert and its different manifestations in Don DeLillo’s work, through a sample of texts published between the Seventies and the first decade of the 21st century. After an introduction aiming at contextualizing the desert in the light of a wider debate about spatial depiction, in the following paraphs the author insists on the pitfalls and mirages of the place, which often becomes the scenery of a ruinous quest for authenticity. A specific attention is paid to the texts, while some important anthropological insights play a key role, allowing a wider consideration on DeLillo’s work. The ability of this writer in interpreting the dynamics of a globalized world will be especially underlined, as well as his capacity for outlining, thanks to the «buried stories» he explores, a feasible alternative to nihilism.